Effect of Bamboo Shoot (Gigantochloa Nigrociliata) Extract on Decreased Blood Pressure and Tnf-Α in Male Wistar Rats (Rattus Norvegicus) - Surati Surati; Lilik Setyowatiningsih; Qurrotu A’yuni Aulia; Santo Yoseph Didik Widiyanto; EM Sutrisna (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Hypertension is a non-communicable disease based on increased pathologies such as RAS, inflammation, and oxidative stress. Bamboo shoot extract contains BSP, phenol, and flavonoids that can reduce inflammatory status, oxidative stress, and ACE. The study aims to determine the effect of bamboo shoot extract on decreased blood pressure and TNF-α in male Wistar Rats made hypertensive.Subjects and Method: This study used a True Experimental Design with the Posttest Only Control Group Design. The study was located at the Integrated Biomedical Laboratory of the Faculty of Medicine, Sultan Agung Islamic University, Semarang in April-July 2021. The study sample of 24 male Wistar Rats was randomly divided into 4 groups. The dependent variables of the study were Blood pressure and TNF-α. The independent variable was bamboo shoot extract. Blood pressure was measured by Pressure Recording Tail Cuff, and TNF-α was measured by using the ELISA method with CATALOG Number KET 9007-48 well. The data were analyzed by using the One Way Anova Test.Results: This study showed no significant difference from systolic or diastolic blood pressure results of male Wistar rats in the K1, K2, and K3 groups after the intervention. Meanwhile, the average levels of TNF-α decreased significantly in the K3 group (Mean= 1.99; SD= 1.13) compared with the control group K0 (Mean= 16.70; SD= 7.45) and it was statistically significant p<0.001.Conclusion: There is no significant effect on blood pressure in male Wistar rats that obtained bamboo shoot extract, but there is a significant effect on TNF-α levels in male wistar rats that obtained bamboo shoot extract.Keywords: bamboo shoots, hypertension, blood pressure, TNF-α, male wistar rat.Correspondence: Surati. Department of Cytohistotechnology, Study Program of Health Analyst, Health Polytechnic, Ministry of Health Semarang. Jl. Wolter Monginsidi No. 115, Pedurungan, Semarang, Central Java, Indonesia, Email: analis_surati@yahoo.com. Mobile: 085226825024.Indonesian Journal of Medicine (2023), 08(01): 121-127https://doi.org/10.26911/theijmed.2023.08.01.12